Challenges for Coexistence of Machine to Machine and Human to Human Applications in Mobile Network: Concept of Smart Mobility Management. (13th December 2012) - Sanyal, Rajarshi; Cianca, Ernestina; Prasad, Ramjee
Abstract : A key factor for the evolution of the mobile networks towards 4G is to bring to fruition high bandwidth per mobile node. Eventually, due to the advent of a new class of applications, namely, Machine-to-Machine, we foresee new challenges where bandwidth per user is no more the primal driver. As an immediate impact of the high penetration of M2M devices, we envisage a surge in the signaling messages for mobility and location management. The cell size will shrivel due to high tele-density resulting in even more signaling messages related to handoff and location updates. The mobile network should be evolved to address various nuances of the mobile devices used by man and machines. The bigger question is as follows. Is the state-of-the-art mobile network designed optimally to cater both the Human-to-Human and Machine-to-Machine applications? This paper presents the primary challenges for the coexistence of M2M and H2H devices in a mobile network and draws emphasis for revisiting the mobility management aspects and congestion control in the-state-of-the-art network. Further, we set out a mobile network architecture with smart mobility management which aims to reduce the signaling interaction between the device and the network to optimise the power and bandwidth.